(untitled) (Journal of Economic Research & Business Administration, 2015)
Urban bus transport, despite the rapid development of private vehicles is and will remain the most important factor that contributes to the livelihoods of the population of the city of Aktau. For most of the population of urban passenger transport is the only means of travel. Much of the population daily travels . Therefore, the level of passenger transportation directly affects the social well-being of the population, which , including the estimated quality of its powers and duties of local authorities. Dissatisfaction with the quality of transport services is one of the major factors shaping the negative public opinion about the level of organization of the process of passenger traffi c in the city. Simultaneously increasing rate of motorization and grow the city’s need for high-quality roads, lengthened length of public transport routes. The main problems in the development of road transport in Aktau are lack of modern automated systems for traffi c management , a high level of road accidents , as well as insecurity in demand for quality transportation passenger transport . Under these conditions, the city of Aktau urgent task is to create a well-functioning system of urban passenger transport capable of ensuring the long-term development of the region . The paper deals with policy priorities urban passenger transport .